Interviews - Elliott Ash; Soumitra Shukla; Jason Sockin (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Interviews allow employers to learn about workers, but do they also enable workers to learn about firms? Studying 500,000 interview reports from Glassdoor, we find candidates for high-paying jobs are more likely to reject a job offer if they believe the interview was easy. Easy interviews appear to convey poor ``fit'' as those who accept offers after easy interviews are two-fifths of a standard deviation less satisfied with their jobs and 10 percent less likely to remain with their employer for at least one year. Analysis of interview narratives using large language models reveals difficult interviews signal colleague ability whereas easy interviews convey a nonselective process. In a small-scale randomized field experiment, an exogenous increase in difficulty elevated perceived difficulty and boosted applicant engagement with the vacancy. Interviews offer workers a preview of match quality, highlighting a channel through which labor markets may become less efficient if firms automate hiring with AI.
Keywords: J24; M50; 330; interviews; peer effects; job satisfaction; large language models